Actual issues of work with the library staff at the present stage of librarianship development - O. V. Makeeva (Библиосфера, 2018)
The problem of working with library personnel is among the most discussed issues in the professional community over several decades. The analysis of publications and reports of public libraries has showed that the list of main topical problems has not changed for years; changes have mainly touched the issue content: the state of vocational education (infrastructure state and development, training quality, students outflow to other professions, interaction of universities and libraries as employers; professional development; the professional culture loss and degradation; the personnel management state; the profession image; the professional community rigidity; information lack on issues of working with personnel. As the most of these problems remain unsolved for several decades, it is possible to characterize the state of studying and taking measures to eliminate them as poorly satisfactory.